Tips on Learning from Context: Formal and Informal Approaches to Under standing the Local Political Economy - Swift, Sarah (USAID, 2018)
Successfully adapting your programmatic efforts and policy engagement to the context depends on maintaining your understanding of that conte xt. Given this, continuous learning and feedback loops–not only about your programming, but also about the environment you are working withi n–are important components of USAID’s work. Since our environments are always changing, in ways big and small, this can be intimidating. One can imagine a scenario where learning consumes the limited time and b udgets available, especially for small programs. The question becomes: How can we learn enough, at the right times, to limit missed opportun ities and warning signs, while avoiding being consumed by data collect ion and analysis that never influences our work? This document capital izes on the experiences of USAID staff as well as emerging learning fr om other donors and researchers to highlight a range of approaches–for mal and informal, time-bound and continuous–that can support ongoing l earning within the operational tempo of a busy Mission team or Operati ng Unit.